The Role of the Basic Sector in Reducing Economic Inequality in the Greater Malang Area - Sishadiyati Sishadiyati; Mohammad Wahed; Noer Aida Triandin (PT Publikasiku Academic Solution, 2024)
The Greater Malang Region, which consists of Malang Regency, Malang City, and Batu City, has great natural resource potential, but still faces challenges in achieving economic consistency. Economic inequality in this region is a concern, especially in the context of the role of basic economic sectors. This study aims to identify the basic economic sectors that play a role in reducing economic inequality in the Greater Malang region and analyze their contribution to the regional economic structure. This study uses a quantitative descriptive approach with Time Series analysis of GRDP in Greater Malang. The analytical tools used include Location Quotient (LQ) Analysis to identify basic and non-basic sectors, and Williamson Index (IW) Analysis to measure the level of economic inequality. The analysis shows that: 1) Malang Regency has basic sectors such as agriculture, industry, and trade; 2) Malang City is dominated by services and education sectors; 3) Batu City has strong agriculture and tourism sectors. Economic inequality in Greater Malang shows a fluctuating trend with an increasing IW value, indicating non-optimization in the development of potential economic sectors. These findings indicate the need to strengthen basic sectors to support more equitable economic growth. While potential exists, more targeted development is needed to reduce inequality and improve community welfare. This study concludes that the basic economic sectors play a key role in reducing economic inequality in Malang Raya. However, the development of these sectors still needs to be optimized to achieve better results in people's economic welfare.